1989
DOI: 10.1016/0014-5793(89)81196-2
|View full text |Cite
|
Sign up to set email alerts
|

Weak interaction of spectrin with phosphatidylcholine‐phosphatidylserine multilayers: A 2H and 31P NMR study

Abstract: Spectrin from human erythrocytes binds to bilayer dispersions of both DMPC and DMPSDMPC (I: 1, w/w). However, no effect of bound spectrin on the conformation of the lipid head groups, as measured from the deuterium quadrupolar splittings of DMPC or DMPS specifically deuterated in the polar head groups, was detected in I:1 mixtures of the two lipids containing either deuterated DMPC or DMPS. Neither the phase transition of the DMPS:DMPC mixtures, nor the spin-lattice relaxation time (T,) of the deuterated DMPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Similar binding curves were obtained for vesicles prepared from the lipids extracted from bovine brain synaptic plasma membranes [21]. K d (dissociation constant) values obtained in these studies (in the nanomolar range) are similar to those obtained previously (see, for example, [22] ; reviewed in [1,23]) for erythrocyte spectrin. In the present studies we applied monolayer and fluorescence quenching techniques to explore this interaction further.…”
Section: Introductionsupporting
confidence: 87%
“…Similar binding curves were obtained for vesicles prepared from the lipids extracted from bovine brain synaptic plasma membranes [21]. K d (dissociation constant) values obtained in these studies (in the nanomolar range) are similar to those obtained previously (see, for example, [22] ; reviewed in [1,23]) for erythrocyte spectrin. In the present studies we applied monolayer and fluorescence quenching techniques to explore this interaction further.…”
Section: Introductionsupporting
confidence: 87%
“…The average effect (compare columns 1 and 2 in Table 1) is a 2 fold diffusion coefficient change, which, most importantly, is the same for both layers. Thus, the interaction of the cytoskeleton with the lipids present in the RBC inner monolayer has no major influence on the phospholipid lateral diffusion constant, as already suggested by previous studies (Chang et al 1981;Maksymiw et al 1987;Calvez et al 1988;Bitbol et al 1989). In addition, PS, PE and PC diffuse at approximately the same rate when in the inner leaflets of intact RBC (Morrot et al 1986), this is also an indication of the limited influence of the proteins on lipid diffusivity.…”
Section: Discussionsupporting
confidence: 65%
“…The earliest published studies on the interaction of spectrin with phospholipids were carried out on extracts mainly consisting of a spectrin-actin mixture [66][67][68]. In the following decade, hydrophobic and amphipathic ligands were discovered to interact with purified spectrin, which confirmed the presence of potentially hydrophobic sites in the spectrin structure [68][69][70][71][72][73][74]. These and later studies have been summarized in previous reviews [75,76].…”
Section: Spectrin Binds the Phospholipid Bilayermentioning
confidence: 80%
“…Early studies of spectrin-lipid interaction, dating back to the nineteen eighties, revealed a larger effect exerted by the protein on the fluidity of mono-and bilayers composed of anionic phospholipids when compared to zwitterionic counterparts [66]. However, the majority of subsequent studies showed that the affinity of purified spectrin is similar for both PS-containing and pure PC vesicles [71,[77][78][79]. Using a pelleting assay approach, Diakowski and Sikorski were first to show the lipid-binding activity of non-erythroid spectrin [80].…”
Section: Spectrin Binds the Phospholipid Bilayermentioning
confidence: 99%